Prolonged Conservative Treatment of Endometrial Cancer Patients: More Than 1 Pregnancy Can Be Achieved. Issue 1 (1st January 2011) - Perri, Tamar; Korach, Jacob; Gotlieb, Walter H.; Beiner, Mario; Meirow, Dror; Friedman, Eddie; Ferenczy, Alex; Ben-Baruch, Gilad
Abstract : Background: Preserving reproductive function in young patients with early endometrial cancer is an accepted concept today. The safety and feasibility of long-term conservative treatment, allowing more than 1 pregnancy, remain to be ascertained. Methods: This study was a retrospective chart review of a 27 women with endometrioid adenocarcinoma of the endometrium, who were treated conservatively at 2 tertiary-care institutions. Treatment comprised oral high-dose progestins with or without a levonorgestrel-releasing intrauterine device. Endometrial biopsy was repeated every 2 to 3 months. Results: Over 7.8 to 412 months (median, 57.4 months), tumors regressed completely in 24 (89%) of 27 patients and partially in 2 patients, with 79% responding within 1 to 17 months. Of the complete responders, 15 (62%) of 24 had a recurrence; 4 underwent hysterectomy, and 11 underwent subsequent progestational treatment. All 11 responded, and 3 subsequently conceived. After 2 to 4 years, 5 patients again had a recurrence, of whom 3 underwent hysterectomy. Overall, 2 patients developed ovarian adenocarcinoma. All patients are currently disease-free. Conception occurred in 14 (51.8%) of 27 patients, in 5 more than once. There were 17 live births, and 2 patients are pregnant. Conclusions: According to our data, prolonged progestational therapy for early-stage endometrial adenocarcinoma, allowing women to conceive, is feasible and apparently does not alter clinical outcome. Patients should be advised of the high recurrence rate and possible concomitant ovarian malignancy.